Cytocompatibility and Antibiofilm Activity of Calcium Hydroxide Mixed with Cyperus articulatus Essential Oil and Bio-C Temp Bioceramic Intracanal Medicament - Cláudia Fernandes de Magalhães Silveira; Carlos Eduardo da Silveira Bueno; Angélica Zaninelli Schreiber (MDPI AG, 2024)
Calcium hydroxide represents the most commonly used intracanal dressing between sessions; however, it may not be effective against all types of microorganisms. Several compounds of plant origin have attracted increasing attention from researchers in recent years. The objective of this study was to evaluate the cytocompatibility and antimicrobial activity of calcium hydroxide associated with the essential oil of Cyperus articulatus and the new bioceramic intracanal medicament Bio-C Temp®. Five experimental groups were designed: group Ca-C. articulatus essential oil; group CHPG-calcium hydroxide associated with propylene glycol; group CHCa-essential oil of C. articulatus associated with calcium hydroxide; and group U-UltraCal® XS; group BCT-Bio-C Temp®. The control group was a culture medium. Cytocompatibility was assessed by the methyltetrazolium (MTT) assay after exposure of the Saos-2 human osteoblast-like cell line to dilutions of commercial products/associations for 24 h and 72 h. The antimicrobial activity against mature Enterococcus faecalis biofilm was evaluated by the crystal violet assay. All commercial products/associations showed a cell viability similar to or even higher than the control group (p > 0.05) for both periods evaluated. C. articulatus essential oil associated or not with calcium hydroxide showed better antibiofilm capacity. C. articulatus associated or not with calcium hydroxide showed superior cytocompatibility and antimicrobial capacity, representing a promissory intracanal medicament.